1970
DOI: 10.3329/jdmc.v20i1.8570
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Typhoid fever among the Children in a Semi Urban Area of Bangladesh

Abstract: Context: In Bangladesh, typhoid fever is a round the year problem which sometimes take epidemic proportions. The reason behind such occurrences are unsafe water supply, defective sewage system and unhygienic food handling practice. This study was designed to find out the prevalence of typhoid fever and related factors like sanitation facilities and food practice among the children of low income group people living in Kamrangir char and its adjacent areas in the semi urban Dhaka. Methodology: Data were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 15 publications
3
11
2
Order By: Relevance
“…This is in contrast to findings in reports of studies in Asia where infants constituted significant proportions of patients compared to children. (6) Male-tofemale ratio was 1.52:1, which is in accordance with the results from other study. 7 The study also showed higher incidence in rural areas (61.2%), similar findings were observed by other study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in contrast to findings in reports of studies in Asia where infants constituted significant proportions of patients compared to children. (6) Male-tofemale ratio was 1.52:1, which is in accordance with the results from other study. 7 The study also showed higher incidence in rural areas (61.2%), similar findings were observed by other study.…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings were observed by earlier studies. 6 Such results might be due to the fact that school age children had more chance of having unsafe drinking water and contaminated food at school from venders on the streets. Naturally, there is a huge scope of contamination in outside food from food handlers, processors and sellers.…”
Section: Discussionmentioning
confidence: 99%
“…But in the present study total was 336 Typhoid patients in which the prevalence was highest 222 (64.16%) in young peoples, the age group of 45-60. The finding of Rahman AKMM et al [27] is not in correlation. This may be since in this area the working age group 4560 who are exposed to infection early in the community.…”
Section: Discussioncontrasting
confidence: 46%
“…In the current study the age group 45-60 shows the highest frequency 222 (64.16%). According to Rahman AKMM et al [27] out of 84, prevalence of Typhoid fever was highest 54 (56.25%) among the school age (5-10year) patients followed by adolescents. But in the present study total was 336 Typhoid patients in which the prevalence was highest 222 (64.16%) in young peoples, the age group of 45-60.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation